THE ROLE OF ENTREPRENEURIAL MARKETING IN IMPROVINGORGANIZATIONAL PERFORMANCE IN THE HOTEL BUSINESS - Muh. Husriadi; La Ode Aris; Harmiaty Bahar (Adisam Publisher, 2025)
The hotel industry is face competition is very tight, so there needs to be method creative and flexible marketing. This study aims to examine how entrepreneurial marketing can help increase hotel organizational performance. The method used is qualitative descriptive in a way collect data through interview in-depth, observation, and analysis of documents involving management as well as hotel staff. The results of the study show that the application of entrepreneurial marketing, through continuous service innovation, adjustments experience guests, creativity in marketing, as well as courage and risk management, can produce significant increase in income, level​ residence, loyalty customers, and the hotel's image. Although thus, there is challenges such as limitations resources, rejection of existing organizational culture, and adaptation to digital technology. Implications from this research highlights the need for human resource development, investment in trusted digital technology, and changes in organizational culture to support the success of marketing strategies innovative in the hospitality sector. This finding contributes both financially and theoretical and practical in developing entrepreneurial marketing in the sector service.